Synergistic enhancement of spinal fusion in preclinical models using low-dose rhBMP-2 and stromal vascular fraction in an injectable hydrogel composite - Hye Yeong Lee; Seong Bae An; Sae Yeon Hwang; Gwang Yong Hwang; Hye-Lan Lee; Hyun Jung Park; Joongkyum Shin; Keung Nyun Kim; Sung Won Wee; Sol Lip Yoon; Yoon Ha (Materials Today Bio)
Spinal fusion surgery remains a significant challenge due to limitations in current bone graft materials, particularly in terms of bioactivity, integration, and safety. This study presents an innovative approach using an injectable hydroxyapatite/β-tricalcium phosphate (HA/β-TCP) hydrogel combined with stromal vascular fraction (SVF) and low-dose recombinant human BMP-2 (rhBMP-2) to enhance osteodifferentiation and angiogenesis. Through a series of in vitro studies and preclinical models involving rats and minipigs, we demonstrated that the hydrogel system enables the sustained release of rhBMP-2, resulting in significantly improved bone density and integration, alongside reduced inflammatory responses. The combination of rhBMP-2 and SVF in this injectable formulation yielded superior spinal fusion outcomes, with enhanced mechanical properties and increased bone mass in both small and large animal models. These findings suggest that this strategy offers a promising and safer alternative for spinal fusion, with strong potential for clinical application.